Mental Health Supports for SOGIE Asylum Seekers in Canada: A Community-Responsive Scoping Review - Aaron Yan-Pui So; Taymy Josefa Caso; Sophie Yohani (Behavioral Sciences, 2026)
While research has investigated the mental health burdens of refugee and asylum seekers with diverse sexual orientation and gender identity and expression (SOGIE), far less attention has been given to what supports their mental health, particularly within the Canadian context. In response to an identified need from a local community organization, this scoping review aimed to identify current approaches that support SOGIE asylum seekers’ mental health in Canada. Using the PRISMA-ScR guidelines, searches took place on 7 and 8 March 2026 across peer-reviewed and grey literature databases indexed in MEDLINE, EMBASE, PsycINFO, CINAHL Plus, LGBTQ+ Source, Scopus, Web of Science, SocIndex, Sociological Abstracts, ERIC, Global Health, ProQuest Dissertations and Theses Citation Index, EBSCO Open Dissertations, ProQuest’s Canadian Research Index, Government of Canada Library, Canadian Council for Refugees Member Organizations, Newcomer Research Library, UNHCR Canada, Egale, and Google. Title, abstract, and full-text screening were completed by two team members, and seven studies met the eligibility criteria outlined. The analysis of four peer-reviewed studies and three grey literature documents suggests that SOGIE asylum seeker mental health should involve emotional and psychological support during the refugee determination process, as well as address social determinants of health. Additionally, the available literature indicated that there must be an awareness of how stigma and mistrust, intersectional challenges, and structural barriers impact how mental health supports are provided to and received by SOGIE asylum seekers in Canada. While having seven included documents primarily based in Ontario and Quebec is a limitation in the evidence, this also provides evidence for the need to conduct further research about SOGIE asylum seeker mental health in other areas of Canada.